Systematic Literature Review: Peran motivasi dan self-efficacy terhadap hasil belajar siswa dalam pembelajaran matematika - Ilyas Reski Aziz; Suparni Suparni; Anita Adinda (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
Low mathematics learning outcomes are often associated with psychological factors, particularly learning motivation and self-efficacy. This study aims to examine the role of learning motivation and self-efficacy in students’ mathematics learning outcomes. A Systematic Literature Review was conducted on 15 articles published between 2020 and 2026, retrieved from Google Scholar, Scopus, and Sinta using the PRISMA framework. The results indicate that learning motivation and self-efficacy generally have a positive and significant impact on learning outcomes, although variations are influenced by contextual factors, research methods, and supporting variables. Furthermore, the literature is dominated by quantitative approaches and studies at the undergraduate level. In conclusion, learning motivation and self-efficacy are key determinants of mathematics learning outcomes; however, limitations in sample scope and research design persist. Future research should adopt mixed-method approaches, include more diverse samples, and incorporate additional contextual variables to provide more comprehensive insights.